Some interesting freshwater algae from Chimdi lake including a new record for Nepal - Raj, Shiva Kumar; Rai, Ram Kumar (Nepalese Journal of Biosciences, 2013)
A preliminary study on algae of Chimdi lake was carried out. A total six freshwater algae viz., Oscillatoria splendida Grev. ex Gom., Cylindrospermum stagnale (Kuetz.) Born. et Flah. f. variabilis Prasad, Gloeotrichia raciborskii Woloszynska var. kashiense Rao, Melosira varians Ag., Crucigenia crucifera (Wolle) Collins and Euastrum spinulosum Delp. var. bellum Scott et Prescott were recorded from Chimdi lake. Euastrum spinulosum var. bellum was recorded for the first time from Nepal. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7499 Nepalese Journal of Biosciences 2 : 118-125 (2012)